Interfacial Grown Zinc Oxide Origami Structure for Broadband Visible Light Driven Photocatalysts. Issue 29 (7th September 2022) - Jia, Guobin; Hupfer, Maximilian; Schulz, Martin; Schmidl, Gabriele; Dellith, Andrea; Diegel, Marco; Müller, Robert; Dellith, Jan; Lindner, Florian; Dietzek‐Ivanšić, Benjamin; Plentz, Jonathan
Abstract: A novel route to synthesize large area ZnO/Zn(OH)2 origami thin films at air/liquid interface is reported. ZnO materials derived from this route show the largest blue‐shifted band‐to‐band emission at 3.85 eV (3.37 eV in bulk ZnO) so far, resulting from the quantum confinement in the ultrathin ZnO/Zn(OH)2 nanosheets. Interband defect levels (IDLs) related broadband photoluminescence is observed from UV to red region by excitation wavelength dependent photoluminescence measurements. The ZnO origami structures show photocatalytic methylene blue degradation (MB‐degradation) activity even under sub‐bandgap visible light illumination from 405 nm to green region at 505 nm, measured by low power monochromatic light emitting diode light sources. From the consistent light absorption, luminescence, and MB‐degradation activity, it can be concluded that the broadband visible light MB‐degradation activity is attributed to photogenerated carriers via IDLs. The 2D ZnO‐nanosheets in the origami structure better solve the dilemma of the IDLs in bulk materials, i.e., they are beneficial for light absorption in visible range but detrimental for enhanced recombination loss of carriers, and they can be quickly extracted to the surface without substantial recombination. This finding makes the ZnO origami a promising candidate for efficient photocatalyst that harvesting the sunlight and for indoor applications. Abstract : ZnO origami structure consisting of quasi 2D nanosheets is grown at the interface of air/liquid. The ZnO origami shows large blue‐shift of the band‐to‐band emission to 3.85 eV, and very broadband visible light driven photocatalytic degradation of methylene blue reaching to the green region at 505 nm, correlating to the carrier generation via interband defect levels.